Relationship between characteristics and the level of public knowledge about hypertension self-medication in kepala sungai village, dusun iii kayu lima, secanggang district, 2023 - Panjaitan, Nurhikmah; Pratama, Bagas Rizky (Journal of Midwifery and Nursing, 2024)
Self-medication is the biggest effort made by the community to deal with  health complaints independently, starting from recognizing the symptoms and illnesses they are experiencing to choosing a treatment method. The level of public  knowledge  about the use of medicines and types of herbal plants are known to  be  able to treat various diseases because they have relatively few side effects compared to chemical medicinal compounds. Hypertension is a degenerative  disease  and  is a disease  that  is experienced  by  many people. Self-medication  is the  method  most  people  use to deal with  health  problems before  going  to  health  service  units  in several  areas or buying  medicines  at the  nearest  pharmacy  without advice from a doctor. This study aims to determine   the  level  of   non-recommendation  from a doctor. This   research  aims to determine the level of community knowledge about hypertension self-medication in the village of Head Sungai Dusun III Kayu Lima Secanggang District in 2023. This  research  is non-experimental with a quantitative descriptive  type  of  research  and  the  type  of  data  used  is  primary data with the  tool  used  in  the form of  a questionnaire  with  the average  community  aged  35 -70  years.Characteristics of respondents based on knowledge, the majority with a sufficient level of knowledge were 21 people (48.80%) and the minority with a good level of knowledge was 3 people (7.00%). The conclusion from this research is that there is no significant relationship between sociodemographics.